Correction: Synthesis and properties of siloxane modified perylene bisimide discotic liquid crystals. Issue 46 (15th November 2022) - Zhang, Tingjie; Sun, Dianming; Ren, Xiangkui; Liu, Lili; Wen, Guanyin; Ren, Zhongjie; Li, Huihui; Yan, Shouke
Abstract : Correction for 'Synthesis and properties of siloxane modified perylene bisimide discotic liquid crystals' by Tingjie Zhang et al., Soft Matter, 2013, 9, 10739–10745, ; https://doi.org/10.1039/C3SM52054D .